Following the academic progress of students who have successfully completed the pre-science course in Mara Institute Of Technology Sarawak / Iris Syawe Seh Ling … [et al.] - Seh Ling, Iris Syawe; Ong, Mooi Lian; Khalid, Khadijah (1999)
This study on Pre-Science graduates of ITM Sarawak was conducted to trace the performance of the Pre-Science graduates in their respective Diploma courses at other ITM campuses. The main objectives of the study were to examine the socio economic background of the Pre-Science graduates, to determine the success rate of the Pre-Science graduates in completing their respective Diploma courses and the effectiveness of the Pre-Science course in providing a second chance to the SPM low achievers. A questionnaire survey was conducted where a total of 113 Pre-Science graduates of ITM Sarawak in ITM Shah Alam, Perlis, Pahang, Perak and Sarawak responded.